Corporation income taxes and the cost of capital: A revision (2012)
The value of debt tax shields in foundational corporate valuation models by Nobel Laureates Modigliani and Miller (MM) continues to be a controversial issue that is central to our understanding of corporate finance. Rather than discounting debt interest payments using a riskless interest rate or unlevered equity rate, the present paper proposes the use of the levered cost of equity. Assuming no bankruptcy risk and no personal taxes, our revised tax model yields an inverted U-shaped firm value function with an interior optimal capital structure. Analyses are extended to Miller's personal tax extension of MM's tax model. Also, implications to corporate capital structure decisions and previous literature are discussed.